Niche partitioning and coexistence of two spiders of the genus Peucetia (Araneae, Oxyopidae) inhabiting Trichogoniopsis adenantha plants (Asterales, Asteraceae) - Villanueva-Bonilla, German Antonio; Safuan-Naide, Suyen [UNESP]; Pires, Mathias Mistretta; Vasconcellos-Neto, Joao (Public Library Science, 2019)
Niche theory suggests that the coexistence of ecologically similar species in the same site requires some form of resource partitioning that reduces or avoids interspecific competition. Here, from July 2013 to December 2015, we investigated spatial niche differentiation at three different scales of two sympatric congeneric spiders, Peucetia rubrolineata and P. flava, along an altitudinal gradient in shaded and open areas in an Atlantic forest in Serra do Japi, SP, Brazil. These spiders are peculiar in that they present an exclusive association with the plant Trichogoniopsis adenantha (Asteraceae). In theory, the coexistence of two Peucetia species could be explained by: (1) microhabitat segregation with individuals from different species occupying different parts of the same plants; (2) mesohabitat segregation with different species using plant in different environments; (3) macrohabitat segregation, where different species would not co-occur along the altitudinal gradient. With respect to micro-habitat use, in both species, different instars used different plant parts, while the same instars of both species used the same type of substrate. However, the two Peucetia species segregated by meso-habitat type, with P. rubrolineata preferring T. adenantha plants in shaded areas and P. flava preferring those in open areas. Our results support the hypothesis of niche partitioning begetting diversity, and highlight the importance of analyzing habitat use at multiple scales to understand mechanisms related to coexistence.